O exercício físico é capaz de melhorar expressão de AMPK e GLUT4 em músculo esquelético de ratos alcoolistas e/ou tabagistas - Florido Neto, Armando Ribeiro [UNESP] (2015)
Alcohol and cigarettes are the lawful psychoactive drugs more consumed in the world, usually being consumed in association. Metabolic alterations are linked to alcohol consumption and tobacco use involving impairment in the expression of proteins related to cellular metabolism. The objective of this study was to evaluate if the regular physical exercise can promote positive effects on the possible impairment related to expression of GLUT4 and AMPK in the skeletal muscle of smoker and/or alcoholic rats. Eighty Wistar rats were divided into 8 groups C:control, S:smoker, A:alcoholic, SA: smoker alcoholic, CE: control exercised, SE: smoker exercised, AE: alcoholic exercised, SAE: smoker alcoholic exercised. Smoker groups were exposed to combustion of four cigarettes, 1h a day, 2x a day, 5x a week for 2 months. A mixture of 10% v/v of ethanol plus water was offered to alcoholic groups. Exercised groups were trained on a treadmill (vel=10 m/min) 5x a week, 1h a day, during two months. Insulin Tolerance Test, Glucose Test tolerance were performed for the insulin sensitivity evaluation. RT-PCR was used for quantification of genes Slc2a4 (codes GLUT4) and Prkaa2 (codes AMPK). Western blotting was used for protein content (GLUT4 and AMPK) analysis. One-way Anova and Student t-test were used to analyze the statistical differences among the groups. P values less than 5% were considered significant. S, A and SA groups showed a reduction in body weight (P< 0.05), and SE, AE and SAE groups showed a normal weight gain compared to the others...